Credit Restructuring Efforts for Micro, Small and Medium Business Debtors at PT. Bank BRI Unit Gianyar (Case Study at CV. Angga Sari Garmen) - I Wayan Angga Pratama; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2023)
Development in the economic field is the main driver of development, micro-enterprises play an important role in development and economic growth, this happens not only in developing countries but also in developed countries. The formulation of the problem in this study is: 1. How is the implementation of credit restructuring for MSME debtors at Bank BRI Gianyar Unit Office?, 2. What are the legal consequences for MSME debtors if the restructuring efforts are not successful? The research method used is a type of normative legal research. The most important part of developing micro-enterprises is business loans obtained from credit obtained from a bank. In an agreement, the debtor sometimes defaults. The problem in this study is the occurrence of default on credit agreements. Default or non-fulfillment of the agreement can occur either intentionally or unintentionally. Parties who commit defaults can occur because they are indeed unable to fulfill these achievements or are also forced to carry out these achievements.